2018
DOI: 10.3389/fmars.2018.00201
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Macrofaunal Communities on the Coastal Filter Function in the Bay of Gdansk, Baltic Sea

Abstract: During three cruises to the Bay of Gdansk, Baltic Sea, the fauna, porewater and bottom water were sampled at stations parallel to the shore and along a transect offshore. Diffusive porewater fluxes were calculated and related to the total net fluxes (TNF) of nutrients. The TNF comprise all nutrients that reach the bottom water from the sediment including diffusive nutrient efflux, discharge from macrozoobenthos and microbial activity. They were determined during in situ incubations using a benthic chamber land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 75 publications
(96 reference statements)
4
27
0
Order By: Relevance
“…Gammal et al (2017) emphasized the increase of solute effluxes of phosphate and ammonium from sediments with decreased macrofaunal activity induced by coastal hypoxia in the western Gulf of Finland. The recent study in the Bay of Gdansk by Thoms et al (2018) determined the greatest impact of macrofauna on sedimentary fluxes at stations where communities were dominated by deep-burrowing polychaetes. The authors suggested that these communities can serve as a descriptive indicator to estimate the extent of the coastal filter, where organic matter is reworked and relatively large amounts of nutrients (NH + 4 , NO − 3 , PO 3− 4 , SiO 2 ) are released into the bottom water.…”
Section: Introductionmentioning
confidence: 99%
“…Gammal et al (2017) emphasized the increase of solute effluxes of phosphate and ammonium from sediments with decreased macrofaunal activity induced by coastal hypoxia in the western Gulf of Finland. The recent study in the Bay of Gdansk by Thoms et al (2018) determined the greatest impact of macrofauna on sedimentary fluxes at stations where communities were dominated by deep-burrowing polychaetes. The authors suggested that these communities can serve as a descriptive indicator to estimate the extent of the coastal filter, where organic matter is reworked and relatively large amounts of nutrients (NH + 4 , NO − 3 , PO 3− 4 , SiO 2 ) are released into the bottom water.…”
Section: Introductionmentioning
confidence: 99%
“…The 50-m depth contour in the BG (Figure 3) separates near-coastal sandy sediments from offshore muddy sediments (Thoms et al, 2018). This differentiation also appears in the LRT, which was longer in the coastal area shallower than 50 m water depth than in the northern offshore area.…”
Section: Spatial Differences Of Lrtmentioning
confidence: 86%
“…The longer surface-water LRT in the near-coastal area may be conducive to the sedimentation of organic matter deriving from primary production on the near-coastal seafloor. This would fuel benthic nutrient turnover, especially nutrient retention via fluxes (Thoms et al, 2018) and nitrification (Bartl et al, 2019), in turn facilitating permanent nutrient-removal processes such as denitrification and burial. Thus, the surface-water LRT may have an indirect impact on the permanent removal of nutrients from this coastal system, which functions on time scales much longer than the mean water residence time (Asmala et al, 2017).…”
Section: Spatial Differences Of Lrtmentioning
confidence: 99%
See 1 more Smart Citation
“…Oceanographic data can be found at the Baltic Environmental Database http:// www.balticnest.org/bed. Sediment data can be found in the supplemental information of Thoms et al (2018). This work was supported by the COCOA project under the BONUS research program funded by the European Commission; the Danish Research Council for Independent Research (DFF-1323-00336); and the German Federal Ministry of Science and Education, BMBF (03F0683A).…”
Section: Acknowledgmentsmentioning
confidence: 99%